Determining the spatial distribution of laser-induced plasma by laser-induced voltaic measurement. (27th August 2021) - Miao, Xinyang; Qin, Qingdong; Liu, Zhi; Zhang, Shanzhe; Zhan, Honglei; Zhao, Kun
Abstract: Distribution characteristics of laser-induced plasma (LIP) plays a significant role in the mechanism studies and applications. Owing to various technologies and limitations, the quantitative analysis of plasma channel distribution has not been fully expounded. Here in this work, laser-induced voltage (LIV) measurement was employed to assess the distribution of LIP channels. An exponential relationship was observed between the energy and the voltage, indicating that the laser energy has a controllable influence on the plasma channel. The distribution of plasma channels is captured by moving the electrode position in two directions. LIV is provided as an innovative method to describe the distribution of plasma channels, which is a promising means for characterizing the formation, diffusion and expansion of plasma.